Communicating User Experience: Applying Local Strategies Research to Digital Media Design - Milburn, Trudy (2015)
Communicating User Experience illustrates how the use of Local Strategies Research (LSR) methodologies enables designers to understand the cultural implications for user actions and practices in a...
Keywords: dept.aa

Modeling the impact of social problem-solving deficits on depressive vulnerability in the broader autism phenotype - Jackson, Scott L. J.; Dritschel, Barbara (Research in Autism Spectrum Disorders, 2016)
The social communication and interaction deficits associated with the autism phenotype can have serious emotional consequences for individuals on the autism spectrum. This can be particularly true during young-adulthood, a period of increased social demands and expectations. The current study investigated the specific role of social problem-solving deficits as a mediator in the relationship between autism phenotype severity and depressive symptomology in young-adults. A sample of 230 university students (48% male) ranging in age from 18 to 30 (M=21.30, SD=2.48) were assessed on autism phenotype expression (Autism-Spectrum Quotient), social problem-solving ability (Social Problem-Solving Inventory, Revised) and depressive symptomology (Beck’s Depression Inventory). Results indicated that deficient social problem-solving skills account for a significant portion of the depressive symptomology associated with increased autism phenotype expression. Path model analysis output suggested that increased expression of the social components of the autism phenotype are associated with both ineffective social problem-solving styles and attitudes, while increased detail orientation discourages the use of an impulsive problem-solving style. The findings of this investigation provide preliminary evidence suggesting that programs designed to improve social problem-solving skills could be beneficial in the reduction of depressive vulnerability for young-adults on the autism spectrum.
Keywords: Autism phenotype expression; Autism-Spectrum Quotient (AQ); Depression; Path model analysis; Social problem solving; University students; dept.aa

Preface: Special Issue—College Experiences for Students with Autism Spectrum Disorder - Jackson, Scott L. J.; Hart, Logan; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Keywords: dept.aa; dept.sed

Translating Tasks for International Classrooms - Townsend, Rebecca M; Milburn, Trudy (Internationalizing the Communication Curriculum in an Age of Globalization, 2019)
This chapter presents a case study from an American university’s partnership with a Polish university. The case involves an assignment to international students studying for their master’s degrees: translating “key concepts in intercultural dialogue” for publication on the Center for Intercultural Dialogue’s website. There were several problems of translation of the task assignment. One problem is the translation of expectations. Learning outcomes occur for professors, too, and the chapter offers reflection on what lessons were realized for future teaching in the international classroom.
Keywords: dept.aa

Post-settlement dispersal and dynamic repopulation of estuarine habitats by adult Mercenaria mercenaria, St. Catherines Island. - Prezant, Robert; Rollins, Harold; Toll, R.B. (Geoarchaeology of St. Catherines and the Georgia Bight, 2011)
Keywords: dept.aa; ⛔ No DOI found

A critical checklist of the Decapod (Arthropoda: Decapoda) of the Atlantic coastal bays of Maryland. - Counts; Prezant, Robert; Chapman, E. (The Maryland historian, 2011)
Keywords: dept.aa; ⛔ No DOI found

Temporal Variation in Molluscan Community Structure in an Urban New Jersey Pond - Chapman, Eric J.; Prezant, Robert S.; Shell, Rebecca (Northeastern Naturalist, 2012)
Barbour's Pond is a 4.45-ha pond located in Garrett Mountain Reservation in Passaic County in northern New Jersey, one of the most densely populated regions in the United States. Despite its small size and surrounding urban sprawl, the shallow waters of this pond hold 18 species of molluscs. Monthly samples from March 2004 through March 2006 found the highest diversity in December 2004, and in January, June, and July 2005. Additional samples were taken in April 2007 and May 2010 to spot-check relative diversity years after the original sampling period. Total molluscan abundance was greatest in July and November 2004, possibly reflecting new late spring and autumn cohorts. Univariate statistics demonstrate that this pond has a temporally stable and diverse malacofauna. Analysis, of basic environmental parameters including temperature and pH, however, showed little correlation with molluscan diversity over time, underscoring the stable yet complex nature of biodiversity of this small urban pond.
Keywords: dept.aa; peer-reviewed

Effects of Upper-Limit Water Temperatures on the Dispersal of the Asian Clam Corbicula fluminea - Rosa, Inês Correia; Pereira, Joana Luísa; Costa, Raquel; Gonçalves, Fernando; Prezant, Robert (PLOS ONE, 2012)
Temperature is a determinant environmental variable in metabolic rates of organisms ultimately influencing important physiological and behavioural features. Stressful conditions such as increasing temperature, particularly within high ranges occurring in the summer, have been suggested to induce flotation behaviour in Corbicula fluminea which may be important in dispersal of this invasive species. However, there has been no experimental evidence supporting this hypothesis. It was already proven that C. fluminea drift is supported by a mucilaginous drogue line produced by mucocytes present in the ctenidia. Detailed microscopic examination of changes in these cells and quantification of clam flotation following one, two and three weeks of exposure to 22, 25 and 30°C was carried out so that the effects of increasing water temperatures in dispersal patterns could be discussed. Results show that changes in temperature triggered an acceleration of the mucocytes production and stimulated flotation behaviour, especially following one week of exposure. Dilution of these effects occurred following longer exposure periods. It is possible that these bivalves perceive changing temperature as a stress and respond accordingly in the short-term, and then acclimate to the new environmental conditions. The response patterns suggest that increasing water temperatures could stimulate C. fluminea population expansion.
Keywords: Analysis of variance; Animal behavior; Behavior; Bivalves; Crystallization; Histology; Invasive species; Sediment; dept.aa; peer-reviewed

Going global: the introduction of the Asian isopod Ianiropsis serricaudis Gurjanova (Crustacea: Peracarida) to North America and Europe - Hobbs, Niels-Viggo; Lazo-Wasem, Eric; Faasse, Marco; Cordell, Jeffery R.; Chapman, John W.; Smith, Carter S.; Prezant, Robert; Shell, Rebecca; Carlton, James T. (Aquatic Invasions, 2015)
The Asian isopod Ianiropsis serricaudis is now well established in fouling communities, often associated with introduced ascidians, throughout the Northern Hemisphere but has gone largely unnoticed because of its diminutive size (typically less than 3 mm in length) and the difficulties of identifying small peracarid crustaceans. Known locations include the northeastern Pacific (Puget Sound, San Francisco Bay, and Monterey Bay), the northwestern Atlantic (from the Gulf of Maine to Barnegat Bay, NJ), and the northeastern Atlantic (England and the Netherlands). We predict that this species is widespread along North America and European coasts, and may already be introduced to cold temperate waters of the Southern Hemisphere as well.
Keywords: Arthropoda; Carcinogenicity; Carcinology; Europe; Ianiropsis serricaudis; Isopoda; Shellfish; ballast water; dept.aa; fouling; introduced species; marine; shipping

Comparative Shell Microstructure of Two Species of Tropical Laternulid Bivalves from Kungkrabaen Bay, Thailand with After-Thoughts on Laternulid Taxonomy - Prezant, Robert S.; Shell, Rebecca M.; Wu, Laying (American Malacological Bulletin, 2015)
The anomalodesmatan family Laternulidae represents a group of bivalves with a very few well-known taxa and many more poorly known taxa. Laternula rostrata (G. B. Sowerby, 1839) and L. anatina (Linnaeus, 1758) occur in close proximity to each other in and along the margins of mangroves of Kungkrabaen Bay, Thailand. Laternula rostrata resides in soft to sandy sediments often within the interstices of mangrove roots located in more open portions of the mangrove mud flat. Laternula anatina lives deeper in the mangrove in more protected environs. Laternula anatina is a smaller bivalve that has a variable shell outline, sometimes a wrinkled shell appearance, thicker periostracum, and frequently extensive umbonal erosion. Both species have high concentrations of external shell spinules anteriorly and closer to the umbos (i.e., in juvenile shell) reflecting functionality in retaining an infaunal position. The larger L. rostrata is thinner shelled and more fragile; has more distinct and longer shell spinules composed of flattened lathes; a glossy external appearance; a longer umbonal slit; and a deeper pallial sinus. Additionally, L. rostrata has a saddle-shaped lithodesma; a lithodesma is absent in L. anatina as is typical of most laternulids. Shell microstructure of both is prismatonacreous, typical of the group, but the prismatic layer is thin and appears truncated into small blocky and/or granular columns in transitional zones. The bulk of the shell is tightly packed sheet nacre. The growth lines in L. rostrata, more pronounced but fewer in number than in L. anatina, appear as shallow rolling “hills” in both the shell and chondrophore. The differences in shell microstructure in these two species are specific to the taxa but based on different habitats and burrowing depths, albeit within the confines of a tropical mangal, could represent biomineralization events that reflect environmental adaptations. Variations in the thickness of the microstructural shell layers of four species of laternulids is compared and we speculate on possible functional and/or environmental relevance of these differences.
Keywords: dept.aa; peer-reviewed

Influence of Diphenhydramine HCl and Caffeine on Embryonic Development and Adult Reproductive Success of the Freshwater Gastropod Helisoma trivolvis - Sanchez, Diana; Prezant, Robert S. (American Malacological Bulletin, 2016)
Diphenhydramine HCl (DH) and caffeine are commonly detected contaminants in waterways and drinking water nationwide (U.S.A.) and yet little is known of their influence on the development of aquatic molluscs. The antihistamine diphenhydramine blocks the chemical effects of histamine by inhibiting the re-uptake of serotonin (5-HT). Caffeine can influence the regulation of calcium (Ca2 ) and neurotransmitters, such as 5- HT, by inhibiting the re-uptake of adenosine. Serotonin receptor-mediated signaling is key during embryonic development in the freshwater snail Helisoma trivolvis (Say 1816). Embryonic development rates of H. trivolvis depend upon external conditions such as oxygen concentration and temperature. We examine the effects of diphenhydramine (DH) and caffeine on development and reproductive potential of this common aquatic snail. Concentrations of DH at 40.0, 50.0 and 60.0 µM affect the in-capsule embryonic development and hatching rate. Caffeine at 40.0, 50.0 and 60.0 µM show no influence to the hatching rates; however, these caffeine concentrations influence the in-capsule embryonic rotation rate. Eight-month observations of adult H. trivolvis reproductive activities show no influence in number of egg masses deposited when exposed to test concentrations of DH or caffeine.
Keywords: dept.aa; peer-reviewed

Growing routes: Rhetoric as the study and practice of movement - Crawford, I.W. (Rhetorica in Motion: Fem. Rhetorical Methods and Methodologies, 2010)
Keywords: dept.aa

Promoting collaboration and cultural competence for physician assistant and physical therapist students: A cross-cultural decentralized interprofessional education (IPE) model. - De Oliveira, Kathleen; North, Sara; Beck, Barbra; Hopp, Jane (Journal of Educational Evaluation for Health Professions, 2015)
PURPOSE: As the United States health care model progresses towards medical teams and the country's population continues to diversify, the need for health professional education programs to develop and implement culturally specific interprofessional education (IPE) becomes increasingly imperative. A wide range of models exists for delivering and implementing IPE in health education, but none have included the cultural components that are vital in educating the health professional., METHODS: A cross-cultural decentralized IPE model for physician assistant (PA) and physical therapy (PT) students was developed. This three-part IPE series was created using an established cultural curricular model and began with the exploration of self, continued with the examination of various dimensions of culture, and concluded with the exploration of the intersection between health and culture. We assessed student satisfaction of the IPE experiences and students' engagement and attitudes towards IPE using a three-item open-ended questionnaire administered after each cross-cultural activity and the Interprofessional Education Series Survey (IESS) upon the completion of the series., RESULTS: IESS responses showed that PA and PT students reported benefits in interprofessional collaboration and cultural awareness and expressed overall satisfaction with the series. Qualitative analysis revealed growth in student response depth consistent with the scaffolded focus of each IPE module in the series., CONCLUSION: The trends in this three-part series suggest that institutions looking to develop culturally inclusive IPE educational initiatives may have success through a decentralized model mirroring the effective cultural progression focused on addressing exploration of self, examination of various dimensions of culture, and exploration of the intersection between health and culture.
Keywords: dept.aa

Challenges of transitioning from a faculty to an administrative role: part 3, from solving problems to managing polarities. - Thompson, Cesarina M (Nurse Educator, 2011)
Many new nursing leaders assuming deanships, assistant, or interim deanships have limited education, experience, or background to prepare them for the job. To assist new deans and those aspiring to be deans, Jana L. Pressler, PhD, RN, and Carole A. Kenner, PhD, RNC-NIC, FAAN, the editors of this department, address common issues, challenges, and opportunities that face academic executive teams, such as negotiating an executive contract, obtaining faculty lines, building effective work teams, managing difficult employees, and creating nimble organizational structure to respond to changing consumer, healthcare delivery, and community needs. In this article, the editors asked guest author, Dr Cesarina Thompson, to discuss the transition process from faculty to administrative role.
Keywords: *Education, Nursing; *Efficiency, Organizational; *Faculty, Nursing; *Leadership; *Nurse Administrators; *Professional Role/px [Psychology]; Curriculum; Education, Nursing; Efficiency, Organizational; Faculty, Nursing; Humans; Leadership; Nurse Administrators; Professional Role; Time Factors; article; curriculum; dept.aa; human; leadership; nurse administrator; nursing education; organization and management; peer-reviewed; professional standard; psychological aspect; time

Challenges of transitioning from a faculty to an administrative role: part 2, moving from individual contributor to group leader. - Thompson, Cesarina M (Nurse Educator, 2011)
Many new nursing leaders assuming deanships, assistant, or interim deanships have limited education, experience, or background to prepare them for the job. To assist new deans and those aspiring to be deans, Jana L. Pressler, PhD, RN, and Carole A. Kenner, PhD, RNC-NIC, FAAN, the editors of this department, address common issues, challenges, and opportunities that face academic executive teams, such as negotiating an executive contract, obtaining faculty lines, building effective work teams, managing difficult employees, and creating nimble organizational structure to respond to changing consumer, healthcare delivery, and community needs. In this article, the editors asked guest author, Dr Cesarina Thompson, to discuss the transition process from faculty to administrative role.
Keywords: *Faculty, Nursing; *Group Processes; *Leadership; *Nurse Administrators; Education, Nursing; Faculty, Nursing; Group Processes; Humans; Leadership; Nurse Administrators; Schools, Nursing; Social Support; article; dept.aa; group process; human; leadership; nurse administrator; nursing education; peer-reviewed; social support

Transitioning from a faculty to an administrative role: part 1, moving from individual to collective accountability. - Thompson, Cesarina M (Nurse Educator, 2011)
Many new nursing leaders assuming deanships, assistant, or interim deanships have limited education, experience, or background to prepare them for the job. To assist new deans and those aspiring to be deans, Jana L. Pressler, PhD, RN, and Carole A. Kenner, PhD, RNC-NIC, FAAN, the editors of this department, address common issues, challenges, and opportunities that face academic executive teams, such as negotiating an executive contract, obtaining faculty lines, building effective work teams, managing difficult employees, and creating nimble organizational structure to respond to changing consumer, healthcare delivery, and community needs. In this article, the editors asked guest author, Dr Cesarina Thompson, to discuss the transition process from faculty to administrative role.
Keywords: *Career Mobility; *Faculty, Nursing/og [Organization & Administration]; *Nurse Administrators/og [Organization & Administration]; *Professional Role; Career Mobility; Employee Performance Appraisal; Faculty, Nursing; Humans; Leadership; Nurse Administrators; Professional Role; United States; article; career mobility; dept.aa; human; leadership; nurse administrator; nursing education; organization and management; peer-reviewed; personnel management; professional standard

Handheld app offering visual support to students with autism spectrum disorders (ASDs) - Zamfir, Bogdan; Tedesco, Robert; Reichow, Brian (2012)
iPrompts® is a software application for handheld devices that provides visual support to individuals with Autism Spectrum Disorders (ASDs). Caregivers use the application to create and present visual schedules, visual countdown timers, and visual choices, to help individuals with ASDs stay organized, understand upcoming events, and identify preferences. The developer of the application, HandHold Adaptive, LLC, initially introduced iPrompts on the iPhone and iPod Touch in May of 2009. The research team from the Center of Excellence on Autism Spectrum Disorders at Southern Connecticut State University conducted a study of iPrompts in 2010, investigating its use by educators working with students with ASDs. Among other findings, educators indicated a desire to present visual supports on a larger, "tablet"-sized display screen, leading the developer to produce an iPad-specific product, iPrompts® XL. Described in this paper are the research effort of iPrompts and subsequent development effort of iPrompts XL. © 2012 Springer-Verlag.
Keywords: ASD; Applications; Autism spectrum disorders; Diseases; Education; Hand held computers; Hand held device; Smartphones; app; application; autism spectrum disorder; dept.aa; handheld device; iPad; iPhone; iPrompts; smartphone; tablet

The potential of repetitive transcranial magnetic stimulation for autism spectrum disorder: A consensus statement - Cole, Eleanor J.; Enticott, Peter G.; Oberman, Lindsay M.; Gwynette, M. Frampton; Casanova, Manuel F.; Jackson, Scott L. J.; Jannati, Ali; McPartland, James C.; Naples, Adam J.; Puts, Nicolaas A. J.; Albein-Urios, Natalia; Barnett, Carol; et al. (Biological Psychiatry, 2019)
Autism spectrum disorder (ASD) affects approximately 1 in 59 children, but there are currently no biomedical treatments available that target the core symptoms (1). Preliminary evidence suggests that repetitive transcranial magnetic stimulation (rTMS) may have the potential to alleviate difficulties experienced by individuals with ASD (2). The evidence supporting the use of rTMS for ASD has led researchers in the field to form a consensus group that has met annually since 2014. Here we summarize discussions from the most recent meeting in May 2017, including recommendations for future research directions.
Keywords: dept.aa; peer-reviewed

Mood Disorders in High-Functioning Autism: The Importance of Alexithymia and Emotional Regulation. - Morie, Kristen P; Jackson, Scott; Zhai, Zu Wei; Potenza, Marc N; Dritschel, Barbara (Journal of Autism and Developmental Disorders, 2019)
Individuals with autism spectrum disorder (ASD) often have co-morbid anxiety and depression. Alexithymia and emotion regulation difficulties are commonly seen in individuals with ASD and in mood disorders. We hypothesized that alexithymia and emotional regulation would mediate the relationship between autistic features and anxiety/depression symptom severity. We collected data about emotional regulation, alexithymia, autistic symptoms and depression/anxiety in a sample of 64 young adults with ASD. We constructed two serial multiple mediator models, using autistic features as the independent variable and anxiety/depression symptoms as outcome variables. The serial relationship between alexithymia and emotional regulation mediated associations between autistic features and depression and anxiety, separately. The findings suggest that targeting alexithymia may benefit therapies designed to alleviate mood disorders in ASD.
Keywords: *Affective Symptoms/px [Psychology]; *Autism Spectrum Disorder/px [Psychology]; *Emotions; *Mood Disorders/px [Psychology]; ASD; Adolescent; Adult; Affective Symptoms; Affective Symptoms/ep [Epidemiology]; Aged; Alexithymia; Anxiety; Anxiety Disorders; Article; Asperger Syndrome; Asperger syndrome; Autism; Autism Spectrum Disorder; Comorbidity; Depression; Emotional regulation; Emotions; Female; Humans; Male; Middle Aged; Mood Disorders; Mood disorders; Self Report; Surveys and Questionnaires; Toronto Alexithymia scale; Young Adult; adolescent; adult; aged; alexithymia; anxiety; anxiety disorder; autism; comorbidity; controlled study; depression; dept.aa; dept.adm; emotion; emotional disorder; emotionality; female; human; major clinical study; male; mental health; middle aged; mood disorder; peer-reviewed; priority journal; psychology; questionnaire; self report; young adult

Microplastic abundances in a mussel bed and ingestion by the ribbed marsh mussel Geukensia demissa. - Khan, Matthew B; Prezant, Robert S (Marine Pollution Bulletin, 2018)
Human activities have generated large quantities of microplastics that can be consumed by filter-feeding organisms as potential food sources. As a result, organisms may experience marked reductions in growth and/or health. To date there has been no investigations connecting microplastics (MPs) with the critically important ribbed mussel Geukensia demissa. Here we examined MP abundances within a bed of G. demissa in New Jersey. Results indicate that MP densities ranged between 11,000-50,000pieces/m2. The abundance of larger MPs (5mm>=1mm) did not vary among sampling sites while the smaller MPs (<1mm) abundances did vary between sampling sites. These smaller MPs also accounted for 79% of MPs recovered from these sites. Based on the higher abundance of smaller MPs, we also investigated MP ingestion/rejection in a laboratory setting. These results confirmed that ribbed mussels can ingest MPs with negative consequences for the buoyancy of plastics rejected in feces and pseudofeces. Copyright © 2018 The Authors. Published by Elsevier Ltd.. All rights reserved.
Keywords: *Bivalvia; *Plastics/an [Analysis]; *Waste Products/an [Analysis]; *Water Pollutants, Chemical/an [Analysis]; Animals; Article; Bivalvia; Contamination; Eating; Filter-feeding organisms; Geukensia demissa; Human activities; Humans; Ingestion; Ingestion (engines); Marine pollution; Microplastic; Microplastics; Molluscs; Mussel bed; New Jersey; Plastics; Sampling site; United States; Waste Products; Water Pollutants, Chemical; abundance; analysis; animal; animal experiment; animal tissue; bivalve; body fluids and secretions; controlled study; dept.aa; eating; feces; filter feeder; growth; human; human activities; ingestion; ingestion rate; marine pollution; marsh; microplastic; mussel; nonhuman; peer-reviewed; plastic; pseudofeces; sampling; unclassified drug; waste; water pollutant

Brief report: Self-reported academic, social, and mental health experiences of post-secondary students with autism spectrum disorder - Jackson, Scott L. J.; Hart, Logan; Brown, Jane Thierfeld; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2018)
Keywords: dept.aa; dept.sed

Visioning hope: embracing higher education's role with urban public charter schools - Bergeron, Bette S. (Urban Education, 2017)
The purpose of this study is to reflect on the evolution of a partnership between a university and urban charter high school serving a predominately African American population. Because of the author's embeddedness both as the researcher and participant member, this research assumes the paradigm of autoethnography. Reflections on key components of this evolution provide implications for teacher education, particularly in regard to a call for engagement between urban charter schools and educator preparation programs, and a challenge to higher education to analyze existing perceptions of public charter schools within a wider institutional mission to prepare educators for all children.
Keywords: African American students; charter school; dept.aa; high school; programs; teacher education; universities; urban education

Transition issues and challenges for youth with autism spectrum disorders - Volkmar, Fred R.; Jackson, Scott L. J.; Hart, Logan (Pediatric Annals, 2017)
Keywords: dept.aa; dept.sed

Autism: Social communication disorder - Jackson, Scott Luther James (Encyclopedia of Autism Spectrum Disorders, 2017)
Keywords: dept.aa